Implementation of Health Promotion in Preventing Dengue Hemorrhagic Fever (DHF) Through the Use of Lemongrass Leaves in Bath Water - Ariana, Diah; Hartono, Hartono; Anantanyu, Sapja; Masykuri, Mohammad (AIBPM Publisher, 2024)
ABSTRACTStudy This aim to analyze implementation promotion health in Prevent Dengue Hemorrhagic Fever (DHF) by use inner lemongrass leaves bathtub. DHF is a disease caused by the dengue virus which is transmitted by the Aedes aegypti mosquito. In Indonesia, dengue fever cases continue increases, with amount fluctuating cases and deaths every year. So that effort Dengue prevention is very important for done. Study This carried out in the District Tambaksari, Surabaya, which is one area endemic dengue fever. Research methods used is studies case with collect data via observation field, interview with various party related health, and data analysis using interactive models. Research result show that Lemongrass plants (Cymbopogon nardus) contain oil essentials, esp citronnelal, which has characteristic larvicide to Aedes aegypti mosquito. Lemongrass can be used done with a number of way, like use lemongrass powder as larvicide and spraying lemongrass spray as a repellent. Study This conclude that use lemongrass leaves as part from promotion health can effective in prevent spread of dengue fever. Steps like use lemongrass as larvicide and repellent can help reduce population Aedes aegypti mosquitoes and reduce risk affected by dengue fever. With Thus, implementation promotion health through you can use lemongrass be an effective strategy in control dengue fever.